Economic Structure and Performance of the Retail Industry - Productivity Commission (Media & Release (Productivity Commission), 2011)
Retailing is an important economic activity as it provides the interface between the production and distribution of goods and their consumption by the Australian community. As well as providing this service, retail is a significant activity in its own right — the retail industry is one of Australia’s largest employers. Currently, there are almost 140 000 retail businesses employing about 1.2 million people or 10.7 per cent of the total working population in 2009-10. The retail industry also makes a significant contribution to economic output, contributing $53 billion or over 4.1 per cent of GDP in 2009-10 (ABS 2010b).
Inquiry reports
Keywords: Government, law and policy; Government, law and policy